Fecal microbiota composition, serum metabolomics, and markers of inflammation in dogs fed a raw meat-based diet compared to those on a kibble diet - Hiney, Kris; Sypniewski, Lara; DeSilva, Udaya; Pezeshki, Adel; Rudra, Pratyaydipta; Goodarzi, Parniyan; Willis, Erin; McFarlane, Dianne (Frontiers in Veterinary Science, 2024)
Despite the potential health risks associated with feeding raw and non-traditional diets, the use of these diets in dogs is increasing, yet the health outcomes associated with these diets is not well understood. This study investigates the effect of feeding dogs a kibble or raw meat-based diets on fecal microbiota composition, serum metabolomics and inflammatory markers.Clinically healthy dogs with a history of consuming either kibble (KD, n= 27) or raw meat-based diets (RMBD, n=28) for more than one year were enrolled. Dogs were fed a standardized diet of either a single brand of KD or RMBD for 28 days. Serum and fecal samples were collected for analysis of microbiota, metabolomics, and inflammatory markers. Multiple regression analysis was performed for each of the metabolites and inflammatory markers, with feed group, age and BCS included as independent variables.The fecal microbiota composition differed between the KD and RMBD groups. Beta-diversity and some indices of alpha-diversity (i.e., Shannon and Simpson) were different between the two diet groups. Sixty-three serum metabolites differed between KD and RMBD-fed dogs with the majority reflecting the differences in macronutrient composition of the two diets.Fecal IAP, IgG and IgA were significantly higher in RMBD dogs compared to KD dogs, while systemic markers of inflammation, including serum c-reactive protein (CRP), galectin, secretory receptor of advanced glycation end-products (sRAGE), haptoglobin, and serum IgG were similar in dogs fed either diet.Diet composition significantly affected fecal microbiota composition and metabolome. Although it had a potentially beneficial effect on local inflammatory markers, feeding RMBD had no impact on systemic inflammation. The influence of these changes on long term health outcomes provides an area for future study.